The memristive response in solids - Silva, Rafael Schio Wengenroth (Universidade Federal de São Carlos, 2023)
In this Master Thesis, we have investigated basic ingredients of the theory of solid state transport, namely the Drude like conductivity and the activation of nonequilibrium charge carriers subjected to a relaxation time, concluding that they are sufficient conditions for a memristive response. These findings point to the natural emergence of memory that, if discernible under adequate set of driving inputs, turns to be the rule and not the exception, with contrasting signatures according to symmetry constraints, either built-in or induced by external factors. Explicit analytical expressions for conductance and content are presented, unveiling very concise and accessible correlations between general intrinsic microscopic parameters such as relaxation times, activation energies, and efficiencies (encountered throughout various fields in Physics) with external drives: voltage pulses, temperature, illumination, etc. Four toy models under different applied bias: sinusoidal and triangular, have been investigated, providing insights about the memory formation, as well as the expressions mentioned above. The model has also been successfully applied to predict and explain memory features in samples based on ZnO thin films that were fabricated and characterized by colleagues, reinforcing its validity. The theory allowed providing values for the system’s fundamental parameters, such as its relaxation time. Finally, the perspectives and directions of the forthcoming research tasks, to be continued on a PhD, are presented, pointing to the extension of the theoretical results by introducing asymmetries in the model and by exploring the topology of the current-voltage characteristics. The model can be extended to other physical systems, such as those based on quantum dots, and by applying the robust mechanism thus far constructed to study, explain, and predict results in experimental realizations, such as in oxide thin films.
A resposta memristva em sólidos
Keywords: Memdevices; Memory; Memristors; Non-equilibrium carriers; Dispositivos com memória; Memória; Memristores; Portadores de não-equilíbrio; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::TRANSP.ELETRONICOS E PROP. ELETRICAS DE SUPERFICIES;INTERFACES E PELICULAS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL